State Responsibility in Protecting Children from Sexual Violence in Educational Settings: A Case Study of Gorontalo - Thalib, Mastura H.; Lisnawaty W. Badu; Karlin Z. Mamu (Siyasah Dusturiyah: State Law Review, 2025)
This study examines the constitutional responsibility of the state in protecting children from sexual violence within educational institutions, using Gorontalo City as a case study. Article 28B paragraph (2) of the 1945 Constitution obliges the state to ensure that every child is protected from violence and discrimination. However, the increasing number of sexual violence cases in schools and the weak institutional response indicate a significant gap between constitutional mandates and their implementation. Employing an empirical juridical approach through interviews with the Women and Children Protection Unit (PPA) of Gorontalo City Police, the Regional Office for Women and Children Protection, and relevant legal documents, this research reveals that the failure of protection is not merely due to criminal factors, but also the lack of institutional governance, inadequate state oversight, weak school-based child protection mechanisms, and limited capacity of law enforcement agencies. These findings demonstrate that the state has not fully carried out its positive obligations to protect children. The study recommends strengthening local regulations, establishing a regional child protection task force, improving the capacity of PPA units, and integrating child-protection policies into school governance as part of the state's constitutional duties.